Guinness World Records, 2020 - Glenday, Craig (Guinness World Records Ltd., 2019)
Presents the biggest, smallest, fastest, longest, and other record setters for 2019 in the categories of space, Earth, animals, humans, fantastic feats, science and technology, arts and media, and sports.